Enhancing Critical Thinking Through Literature Circles in EFL Classrooms: Empirical Evidence and Contributions to SDG 4 - Junie Darmaningrum; Lies Amin Lestari; Pratiwi Retnaningdyah (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
-